Antibacterial negative ion ceramic tile and preparation process thereof

By using nano -oxidation and silicon nano -silicon microfilling as antibacterial agents in antibacterial tiles, and conducting quality ratio and modified treatment, the existing antibacterial tiles are not lasting. Effect.

CN119371179APending Publication Date: 2025-01-28HEBEI YANGSHI TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411602001.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The antibacterial effect of existing antibacterial ceramic tiles is not long-lasting and cannot achieve the expected antibacterial effect in actual use.

Method used

The nano oxide and silicon nano -silicon microfillings are used as antibacterial agents, and the antibacterial activity and decentralized state are enhanced by regulating its quality ratio and modification treatment, and the long -term bacteriostatic effect of tiles is improved.

Benefits of technology

The long -term antibacterial effect of tiles is achieved, the efficiency of bacteriostatic efficiency is significantly improved, and it can more durate the normal function of bacterial cell membranes and destroy the internal environment of bacteria.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of antibacterial ceramic tiles, and provides an antibacterial negative ion ceramic tile and a preparation process thereof.The antibacterial negative ion ceramic tile is prepared from, by weight, 20-30 parts of clay, 30-40 parts of kaolin, 10-20 parts of feldspar, 5-10 parts of kieselguhr and 1-3 parts of antibacterial agent, the antibacterial agent comprises nano zirconium oxide and silver-loaded nano silicon micro powder, the mass ratio of the nano zirconium oxide to the silver-loaded nano silicon micropowder is (1: 9)-(9: 1). According to the technical scheme, the problem that the antibacterial effect of the ceramic tile is not lasting in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antibacterial tiles, and in particular to an antibacterial negative ion tile and a preparation process thereof. Background Art

[0002] In today's building materials field, people's requirements for indoor environmental quality are increasing day by day. They not only pay attention to the beauty and practicality of materials, but also have higher expectations for their health and environmental protection performance.

[0003] Negative ions refer to oxygen ions that have gained extra electrons and are negatively charged, usually represented by "O 2- "It means. It is the free electrons produced by the ionization of molecules in the air under the action of high pressure or strong rays, most of which are obtained by oxygen. In nature, negative ions are widely present in forests, waterfalls, seaside environments and other environments. The air in these places usually makes people feel fresh and comfortable.

[0004] Negative ions can combine with dust, smoke and other particles in the air, causing them to condense into larger particles, making it easier for them to settle to the ground, effectively reducing suspended particulate matter in the air and reducing the harm of haze and other factors to human health. They have strong redox capabilities and can decompose harmful chemical gases such as formaldehyde, benzene, and ammonia in the air; they can convert these harmful gases into harmless substances such as carbon dioxide and water, effectively improving indoor air quality and creating a healthy living and working environment for people.

[0005] There are many tiles with antibacterial functions on the market, but the antibacterial properties of some products may not last long, or they may not achieve the expected antibacterial effect during actual use. Negative ions have many significant benefits in improving air quality and promoting human health. Combining the negative ion function with tiles and developing long-lasting antibacterial negative ion tiles can not only provide people with beautiful and durable building decoration materials, but also create a healthier and more comfortable indoor environment for people, which has broad market prospects and application value. Summary of the invention

[0006] The present invention provides an antibacterial negative ion ceramic tile and a preparation process thereof, which solves the problem that the antibacterial effect of the ceramic tile is not lasting in the related art.

[0007] The technical solution of the present invention is as follows: The present invention proposes an antibacterial negative ion tile, comprising the following raw materials by weight: 20-30 parts of clay, 30-40 parts of kaolin, 10-20 parts of feldspar, 5-10 parts of diatomaceous earth, and 1-3 parts of antibacterial agent; The antibacterial agent comprises nano zirconium oxide and silver-loaded nano silicon powder, and the mass ratio of the nano zirconium oxide to the silver-loaded nano silicon powder is 1:9-9:1.

[0008] As a further technical solution, the mass ratio of the nano zirconium oxide to the silver-loaded nano silicon powder is 1:2-3.

[0009] As a further technical solution, the nano zirconium oxide is modified by a modifier, the modifier is 3-(diethoxymethylsilyl)propylamine, and the mass ratio of the modifier to the nano zirconium oxide is 1-2:20.

[0010] In the present invention, the nano zirconium oxide is modified to increase the antibacterial active sites, improve the dispersion state of the nano zirconium oxide in the ceramic tile, increase the antibacterial efficiency, and better exert the long-term antibacterial effect of the ceramic tile.

[0011] As a further technical solution, the preparation method of the modified nano-zirconium oxide comprises the following steps: dispersing the nano-zirconium oxide in a solution, adding a modifier, stirring, centrifuging and washing to obtain the modified nano-zirconium oxide.

[0012] As a further technical solution, the preparation of the silver-loaded nano-silicon powder includes the following steps: the nano-silicon powder is activated and then dispersed in a silver ion solution, and the silver-loaded nano-silicon powder is obtained by filtering and drying after a hydrothermal reaction.

[0013] As a further technical solution, the silver ion loading amount of the silver-loaded nano-silicon powder is 3wt%~5wt%.

[0014] The present invention also provides a preparation process of antibacterial negative ion ceramic tiles, comprising the following steps: S1, raw material preparation: weigh the raw materials in parts by weight, mix, ball-mill and age to obtain a mixture; S2, compression molding: compressing the mixture to obtain a green body; S3, green body sintering: the green body is sintered and cooled to obtain sintered tiles; S4. Surface treatment: polishing, antifouling and super-bright treatment are performed on the obtained sintered ceramic tiles to obtain antibacterial negative ion ceramic tiles.

[0015] As a further technical solution, the ball milling method is wet ball milling, the particle size of the mixture after ball milling is 500-600 mesh, and the aging time is 40-60 hours.

[0016] As a further technical solution, the pressing pressure is 400~420MPa.

[0017] As a further technical solution, the sintering temperature is 1250~1350℃.

[0018] As a further technical solution, the steps of the ultra-clean and bright treatment include edge grinding and chamfering, cleaning and drying, and surface waxing.

[0019] The working principle and beneficial effects of the present invention are: In the present invention, nano zirconium oxide and silver-loaded nano silicon powder are added as antibacterial agents, and their mass ratio is adjusted to give full play to their synergistic effect, thereby interfering with the normal function and structural integrity of bacterial cell membranes, destroying the internal environment of bacteria, and improving the long-term antibacterial effect of tiles. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] In the following examples and comparative examples: Nano silicon powder: particle size is 30nm, spherical; Nano zirconium oxide: The average particle size is 30nm.

[0022] Example 1 The preparation of silver-loaded nano-silicon powder includes the following steps: weighing 2 parts of nano-silicon powder and dispersing them in 20 parts of hydrochloric acid solution with a concentration of 10wt%, stirring at 60°C for 3h, filtering to obtain acid-treated nano-silicon powder, placing the acid-treated nano-silicon powder in a high-temperature furnace and heating it to 800°C, keeping it warm for 3h, cooling to obtain activated nano-silicon powder, dispersing the activated nano-silicon powder in a silver nitrate solution, transferring it to a reactor and heating it to 120°C for hydrothermal reaction for 6h, filtering and drying to obtain silver-loaded nano-silicon powder, wherein the silver ion loading amount of the silver-loaded nano-silicon powder is 3wt%; A preparation process of antibacterial negative ion ceramic tiles comprises the following steps: S1. Raw material preparation: weigh 20 parts of clay, 30 parts of kaolin, 10 parts of feldspar, 5 parts of diatomaceous earth and 1 part of antibacterial agent, mix them evenly, use wet ball milling to a particle size of 500 mesh, and age for 40 hours to obtain a mixture; wherein the 1 part of antibacterial agent includes nano zirconium oxide and silver-loaded nano silicon powder in a mass ratio of 1:1; S2, compression molding: the mixture is compressed and molded at a pressure of 400 MPa to obtain a green body; S3, green body sintering: the green body is heated to 1250℃ for sintering, the sintering and heat preservation time is 1.5h, and the sintered ceramic tile is obtained after air cooling to room temperature; S4, surface treatment: polishing, antifouling and chamfering the sintered tiles, cleaning and drying, and waxing the surfaces to obtain antibacterial negative ion tiles.

[0023] Example 2 The preparation of silver-loaded nano-silicon powder includes the following steps: weighing 2 parts of nano-silicon powder and dispersing them in 20 parts of hydrochloric acid solution with a concentration of 10wt%, stirring at 60°C for 3h, filtering to obtain acid-treated nano-silicon powder, placing the acid-treated nano-silicon powder in a high-temperature furnace and heating it to 800°C, keeping it warm for 3h, cooling to obtain activated nano-silicon powder, dispersing the activated nano-silicon powder in a silver nitrate solution, transferring it to a reactor and heating it to 120°C for hydrothermal reaction for 6h, filtering and drying to obtain silver-loaded nano-silicon powder, wherein the silver ion loading amount of the silver-loaded nano-silicon powder is 3wt%; A preparation process of antibacterial negative ion ceramic tiles comprises the following steps: S1. Raw material preparation: weigh 25 parts of clay, 35 parts of kaolin, 15 parts of feldspar, 8 parts of diatomaceous earth, and 2 parts of antibacterial agent, mix them evenly, use wet ball milling to a particle size of 550 mesh, and age for 50 hours to obtain a mixture; wherein 1 part of the antibacterial agent includes nano zirconium oxide and silver-loaded nano silicon powder in a mass ratio of 1:1; S2, compression molding: the mixture is compressed and molded at a pressure of 410 MPa to obtain a green body; S3, green body sintering: the green body is heated to 1300℃ for sintering, the sintering and heat preservation time is 1.5h, and the sintered tile is obtained after air cooling to room temperature; S4, surface treatment: polishing, antifouling and chamfering the sintered tiles, cleaning and drying, and waxing the surfaces to obtain antibacterial negative ion tiles.

[0024] Example 3 The preparation of silver-loaded nano-silicon powder includes the following steps: weighing 2 parts of nano-silicon powder and dispersing them in 20 parts of hydrochloric acid solution with a concentration of 10wt%, stirring at 60°C for 3h, filtering to obtain acid-treated nano-silicon powder, placing the acid-treated nano-silicon powder in a high-temperature furnace and heating it to 800°C, keeping it warm for 3h, cooling to obtain activated nano-silicon powder, dispersing the activated nano-silicon powder in a silver nitrate solution, transferring it to a reactor and heating it to 120°C for hydrothermal reaction for 6h, filtering and drying to obtain silver-loaded nano-silicon powder, wherein the silver ion loading amount of the silver-loaded nano-silicon powder is 3wt%; A preparation process of antibacterial negative ion ceramic tiles comprises the following steps: S1. Raw material preparation: weigh 30 parts of clay, 40 parts of kaolin, 20 parts of feldspar, 10 parts of diatomaceous earth, and 3 parts of antibacterial agent, mix them evenly, use wet ball milling to a particle size of 600 mesh, and age for 60 hours to obtain a mixture; wherein the 3 parts of antibacterial agent include nano zirconium oxide and silver-loaded nano silicon powder in a mass ratio of 1:1; S2, compression molding: the mixture is compressed and molded at a pressure of 420 MPa to obtain a green body; S3, green body sintering: the green body is heated to 1350℃ for sintering, the sintering and heat preservation time is 1.5h, and the sintered ceramic tile is obtained after air cooling to room temperature; S4, surface treatment: polishing, antifouling and chamfering the sintered tiles, cleaning and drying, and waxing the surfaces to obtain antibacterial negative ion tiles.

[0025] Example 4 Compared with Example 1, the difference of Example 4 is that one part of the antibacterial agent includes nano zirconium oxide and silver-loaded nano silicon powder in a mass ratio of 1:2.

[0026] Example 5 Compared with Example 1, the difference of Example 5 is that one part of the antibacterial agent includes nano zirconium oxide and silver-loaded nano silicon powder in a mass ratio of 1:3.

[0027] Example 6 Compared with Example 1, the difference of Example 6 is that one part of the antibacterial agent includes nano zirconium oxide and silver-loaded nano silicon powder in a mass ratio of 1:4.

[0028] Example 7 Compared with Example 5, the difference of Example 7 is that 1 part of the antibacterial agent includes modified nano-zirconium oxide and silver-loaded nano-silicon powder in a mass ratio of 1:3, and the preparation method of the modified nano-zirconium oxide includes the following steps: dispersing 4 parts of nano-zirconium oxide in 50 parts of ethanol, adding 0.1 parts of 3-(diethoxymethylsilyl)propylamine, stirring at 25°C for 24 hours, washing with ethanol three times after centrifugation, and drying to obtain modified nano-zirconium oxide.

[0029] Example 8 Compared with Example 7, the difference of Example 8 is that the amount of 3-(diethoxymethylsilyl)propylamine added during the preparation of the modified nano-zirconium oxide is 0.2 parts.

[0030] Example 9 Compared with Example 7, the difference of Example 9 is that the amount of 3-(diethoxymethylsilyl)propylamine added during the preparation of the modified nano-zirconium oxide is 0.4 parts.

[0031] Example 10 Compared with Example 7, the difference of Example 10 is that the amount of 3-(diethoxymethylsilyl)propylamine added during the preparation of the modified nano-zirconium oxide is 0.6 parts.

[0032] Embodiment 11 Compared with Example 9, the difference in Example 11 is that the silver ion loading amount of the silver-loaded nano-silicon powder is 4 wt %.

[0033] Example 12 Compared with Example 9, the difference in Example 12 is that the silver ion loading amount of the silver-loaded nano-silicon powder is 5 wt %.

[0034] Comparative Example 1 Compared with Example 1, the difference of Comparative Example 1 is that one part of the antibacterial agent is only nano zirconium oxide.

[0035] Comparative Example 2 Compared with Example 1, the difference of Comparative Example 2 is that one part of the antibacterial agent is only silver-loaded nano-silicon powder.

[0036] The samples prepared in Examples 1 to 12 and Comparative Examples 1 to 2 were tested as follows: 1. Antibacterial rate: According to the test method specified in JC / T 897-2014 "Antibacterial Performance of Antibacterial Ceramic Products", the antibacterial rate of the test sample is tested.

[0037] 2. Antibacterial durability and antibacterial rate: According to the test method specified in JC / T 897-2014 "Antibacterial Performance of Antibacterial Ceramic Products", the antibacterial durability and antibacterial rate of the test samples are tested.

[0038] The test results are shown in the following table: Table 1 Performance test results of antibacterial negative ion tiles prepared in Examples 1 to 12 and Comparative Examples 1 to 2

[0039] Compared with Example 1, only nano-zirconia was added as an antibacterial agent in Comparative Example 1, and only silver-loaded nano-silicon powder was added as an antibacterial agent in Comparative Example 2. As a result, the antibacterial rate and antibacterial durability of Example 1 were greater than those of Comparative Examples 1 and 2, indicating that nano-zirconia and silver-loaded nano-silicon powder play a synergistic role and can enhance the long-term antibacterial performance of antibacterial negative ion tiles. Compared with Example 1, Examples 4 to 6 added nano-zirconia and silver-loaded nano-silicon powder in different mass ratios. As a result, the antibacterial rate and antibacterial durability of Examples 4 and 5 were greater than those of Examples 1 and 6, indicating that when the mass ratio of nano-zirconia and silver-loaded nano-silicon powder is 1:2~3, the long-term antibacterial performance of the antibacterial negative ion tiles obtained is better.

[0040] Compared with Example 5, Examples 7 to 10 added modified nano-zirconia, and the antibacterial rate and antibacterial durability of Examples 7 to 10 were greater than those of Example 5, indicating that modified nano-zirconia can improve the long-term antibacterial performance of antibacterial negative ion tiles. Modifiers and nano-zirconia were added in different mass ratios in Examples 7 to 10, and the antibacterial rate and antibacterial durability of Examples 8 and 9 were greater than those of Examples 7 and 10, indicating that when the mass ratio of the modifier to nano-zirconia was 1 to 2:20, the long-term antibacterial performance of the antibacterial negative ion tiles obtained was better.

[0041] Compared with Example 9, Examples 11 and 12 added silver-loaded nano-silicon powder with different silver ion loadings. As a result, the antibacterial rate and antibacterial durability of Example 11 were greater than those of Examples 9 and 12, indicating that when the silver ion loading of the silver-loaded nano-silicon powder was 4wt%, the obtained antibacterial negative ion ceramic tile had better long-term antibacterial performance.

[0042] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An antibacterial negative ion tile, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of clay, 30-40 parts of kaolin, 10-20 parts of feldspar, 5-10 parts of diatomaceous earth and 1-3 parts of antibacterial agent, wherein the antibacterial agent comprises nano zirconium oxide and silver-loaded nano silicon powder, and the mass ratio of the nano zirconium oxide to the silver-loaded nano silicon powder is 1:9-9:

1.

2. The antibacterial negative ion tile according to claim 1, characterized in that: The mass ratio of the nano zirconium oxide to the silver-loaded nano silicon powder is 1:2-3.

3. The antibacterial negative ion tile according to claim 1, characterized in that: The nano zirconium oxide is modified by a modifier, the modifier is 3-(diethoxymethylsilyl)propylamine, and the mass ratio of the modifier to the nano zirconium oxide is 1-2:

20.

4. The antibacterial negative ion tile according to claim 1, characterized in that: The preparation of the silver-loaded nano-silicon powder comprises the following steps: the nano-silicon powder is activated and then dispersed in a silver ion solution, and the silver-loaded nano-silicon powder is obtained by filtering and drying after hydrothermal reaction.

5. The antibacterial negative ion tile according to claim 1, characterized in that: The silver ion loading amount of the silver-loaded nano-silicon powder is 3wt%-5wt%.

6. The preparation process of an antibacterial negative ion tile according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, raw material preparation: weigh the raw materials in parts by weight, mix, ball-mill and age to obtain a mixture; S2, compression molding: compressing the mixture to obtain a green body; S3, green body sintering: the green body is sintered and cooled to obtain sintered tiles; S4. Surface treatment: polishing, antifouling and super-bright treatment are performed on the obtained sintered ceramic tiles to obtain antibacterial negative ion ceramic tiles.

7. The preparation process of the antibacterial negative ion ceramic tile according to claim 6, characterized in that: The ball milling method is wet ball milling, the particle size of the mixture after ball milling is 500-600 mesh, and the aging time is 40-60 hours.

8. The preparation process of the antibacterial negative ion ceramic tile according to claim 6, characterized in that: The pressing pressure is 400-420 MPa.

9. The preparation process of the antibacterial negative ion ceramic tile according to claim 6, characterized in that: The sintering temperature is 1250-1350°C.

10. The preparation process of antibacterial negative ion ceramic tile according to claim 6, characterized in that: The steps of the ultra-clean and bright treatment include edge grinding and chamfering, cleaning and drying, and surface waxing.

Citation Information

Patent Citations

  • Aqueous nano zirconia particle paint and method for preparing paint film thereof

    CN102031026A

  • Phenolic resin coated ceramic powder for laser 3D printing and preparation method thereof

    CN105669208A

  • Antibacterial ceramic tile and production method thereof

    CN109851396A

  • Method for preparing antibacterial deodorization ceramic

    CN110451803A

  • Antibacterial and antiviral glaze, antibacterial and antiviral ceramic and preparation method thereof

    CN112279517A